The Effectiveness of Virtual Reality-Based Balinese Gamelan Selonding (Gambling) Music On Anxiety And Blood Pressure In The Elderly - A.A Bagus Suryantara; Ari Wina Sani; I Made Hendra Wijaya (CV. Inara, 2025)
Aging brings with it the consequence of an increase in various cardiovascular diseases, one of which is hypertension. Long-term use of antihypertensive drugs can cause various side effects, one of which is mental changes, thus non-pharmacological therapies such as music therapy are needed. There are many types of music therapy that can be applied, one of which is traditional music (gamelan). There are inconsistencies in previous research, so a combination of Balinese gamelan selonding music therapy with VR or Virtual Reality is needed. VR has become one of the leading innovations in the field of health and wellness, especially in the context of therapy and rehabilitation. The purpose of this study is to determine the effectiveness of VR-based Balinese gamelan selonding music therapy in reducing anxiety and blood pressure in the elderly with hypertension. The research method uses a quasi-experimental pre-post control group design. The sampling technique is purposive sampling according to inclusion and exclusion criteria. The instruments in this study used an anxiety questionnaire, tensimeter, MP3/handphone, earphones and a VR Box. The results of this study show that the provision of VR-based Balinese gamelan selonding music therapy can reduce anxiety and blood pressure in the elderly.